2010
DOI: 10.1080/17470210902925312
|View full text |Cite
|
Sign up to set email alerts
|

The role of timing deviations and target position uncertainty on temporal attending in a serial auditory pitch discrimination task

Abstract: Listeners were presented with sequences of tones that ascended in semitone intervals. On each trial a single target tone in the sequence was displaced in pitch, and listeners were required to indicate whether the target tone was higher or lower than its normal pitch. Task constraints, specifically target serial position uncertainty and the probabilistic relationship between time deviations and target tones, were varied in order to determine the impact of task constraints on temporal attending strategy. When li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
0
15
2
Order By: Relevance
“…RTs did not show a U-shaped pattern benefitting in synchrony targets. Although this contradicts previous rhythmic cueing studies using RTs (e.g., Martin et al, 2005;Sanabria, Capizzi, Correa, 2011) andaccuracy (Herrmann et al, 2016;Lawrance et al, 2014;Rohenkohl et al, 2012), there are also studies which do not support the DAT and even reporting detrimental effects of performance when presenting stimuli in synchrony with a rhythm (Barnes and Johnston, 2010;Spaak et al, 2014;Hickok et al, 2015;Large & Jones, 1999, Experiment 1). For example, Barnes and Johnston (2010) observed that when the target could appear at several different positions in a trial, there was a U-shaped pattern with worse performance for targets in synchrony compared to out of synchrony with the rhythm (Experiment 1).…”
Section: Discussioncontrasting
confidence: 56%
“…RTs did not show a U-shaped pattern benefitting in synchrony targets. Although this contradicts previous rhythmic cueing studies using RTs (e.g., Martin et al, 2005;Sanabria, Capizzi, Correa, 2011) andaccuracy (Herrmann et al, 2016;Lawrance et al, 2014;Rohenkohl et al, 2012), there are also studies which do not support the DAT and even reporting detrimental effects of performance when presenting stimuli in synchrony with a rhythm (Barnes and Johnston, 2010;Spaak et al, 2014;Hickok et al, 2015;Large & Jones, 1999, Experiment 1). For example, Barnes and Johnston (2010) observed that when the target could appear at several different positions in a trial, there was a U-shaped pattern with worse performance for targets in synchrony compared to out of synchrony with the rhythm (Experiment 1).…”
Section: Discussioncontrasting
confidence: 56%
“…They speculated that this effect is based on attentional capture and a purely reflexive adaptive shift of attention in time toward the temporal locus of the target sound. Jones and colleagues have confirmed these general findings in several related or follow-up studies (Jones et al, 2006;Ellis and Jones, 2010;Barnes and Jones, 2000;Barnes and Johnston, 2010).…”
Section: Psychophysical Detection and Discrimination In Forward Entrainmentmentioning
confidence: 60%
“…Several studies have shown that the entrainment phase dissociates from the entraining stimulus phase. Some studies have shown an antiphasic effect (Hickok et al, 2015;Farahbod et al, 2020;Spaak et al, 2014;Simon and Wallace, 2017) while others have shown an in-phase effect (Jones et al, 2002;Ellias and Jones, 2010;Barnes and Johnston, 2010) or even a subject-dependent entrainment phase (Henry and Obleser, 2012) which may be explained by listening strategy (see section 2.3 in the current paper on how off-frequency listening and different attentional strategies may explain Henry and Obleser's behavioral data). Further evidence in support of an attentional mechanism is that the effect seems critically dependent on signal-level uncertainty, at least in tone-in-noise detection tasks where switching to a block design eliminates forward entrainment and reintroducing uncertainty recovers the effect in the same subjects.…”
Section: Simultaneous Vs Forward Entrainmentmentioning
confidence: 77%
“…Note also that Bauer et al (2015) reported performance between .48 and .68 (with chance level at .33) and yet observed no temporal expectancy profiles. This is not the first report of difficulties replicating temporal expectancy profiles (Barnes & Johnston, 2010;Bauer et al, 2015;, but the current study is unique in its variety of task domains (comparisons of pitches, timbres, loudnesses, and durations), addition of the probability manipulation (Experiment 1), and extent of statistical power. The largest contribution of the current data is that temporal expectancies are limited to temporal tasks in the context of standard/comparison judgments.…”
Section: Discussionmentioning
confidence: 90%